Budaya Politik dalam Masyarakat Pragmatis - Sumartono Sumartono (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
General elections and regional head elections in Indonesia are conducted directly. The pattern of community participation is changed. The emergence of pragmatism or political pragmatism in society becomes an interesting political culture to study. Practically, pragmatism means a condition that encourages people to get benefits instantly. As a result, people take any actions to make it happen. In reality, pragmatism not only affects the upper classes (those with a high level of education) but also ordinary people (lower class society or those with low levels of political education). The development of money politics, cow trade politics, the sale of votes, or the existence of political dowry is a sign that there has been a political transaction becoming one of the indicators of pragmatism reality in society